PENGARUH PENGGUNAAN CARBON CLEANER TERHADAP PERFORMA MESIN PADA SEPEDA MOTOR YAMAHA JUPITER Z CW - Kurniawan, Rahman Ade (Jurnal Teknik Mesin, 2019)
Vehicle maintenance is considered very important in increasing the efficiency of fuel use so that it affects engine performance. Additive substances are ingredients that are added to motorized vehicle fuels, which are used to provide an increase in certain basic properties of fuel. Addition of carbon cleaner additives that can erode carbon deposits caused by incomplete combustion in the combustion chamber and cleaning the fuel lines. The results of this study indicate that the use of a carbon cleaner can improve engine performance where at 1400 Rpm torque increases 1.95Kg.m after the use of a carbon cleaner. the biggest power is 4200 Rpm, 12.07 hp. The vehicle exhaust emission test shows the results of the average exhaust gas emissions which have decreased after using a carbon cleaner. At 4200 Rpm of CO exhaust emissions produced showed a decrease after using a carbon cleaner which was from 4.005% to 3.017%, decreasing 0.988%. At 4200 Rpm the resulting HC exhaust emissions showed a decrease after using a carbon cleaner from 107 ppm to 80 ppm, decreasing by 27 ppm. At 4200 Rpm of CO2 exhaust decreased from 3.76% to 2.48%, down 1.28%.Keywords: Carbon Cleaner, Engine Performance,additive